The Mobilization Of South Sumatran Youth During The Japanese Occupation (1942-1945) - Muhammad Akhdan Hariizan; Abd Rahman Hamid; Uswatun Hasanah (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
This study examines the mobilization of youth in South Sumatra through the formation of Gyugun during the Japanese occupation from 1942 to 1945. It aims to explain the strategic reasons behind Japan’s decision to designate South Sumatra as a defense base, analyze the mechanisms of youth mobilization, and identify its impact on national consciousness and the formation of Indonesia’s military forces. The research employs the historical method, including the stages of heuristics, source criticism, interpretation, and historiography. Primary sources consist of the newspaper “Kita Sumatora Shinbun” (1944) and combined with supporting secondary sources in the form of two books authored by Alamsjah Ratu Perwiranegara. The findings indicate that South Sumatra held strategic importance due to its geographical location and petroleum resources, which were vital to Japanese military operations. Youth mobilization was carried out through propaganda, selective recruitment, and intensive military training in Pagar Alam, Karang Dalo, and Palembang under strict Bushido discipline. However, this policy proved paradoxical, as Gyugun training intended to produce loyal defense units instead fostered national awareness, covert resistance, and laid the foundation for the establishment of the BKR, TKR, and ultimately the Indonesian National Armed Forces (TNI). The study concludes that Gyugun mobilization exhibited a dual character: while strengthening Japanese control, it simultaneously served as an incubator of nationalism that gave rise to Indonesia’s national military forces.